Imperialism Above and Below the Water Line: Making Space Up (and Down) in a Colonial Port City. Issue 8 (16th November 2020) - Hofmeyr, Isabel
Abstract : This essay discusses postcolonial space both above and below the water line with a focus on Durban harbour. The essay begins underwater and examines how shipping and harbour engineering created new habitats in the port. The focus then moves onto land and considers two spaces: the Custom House and the space created by the mainly Zulu-speaking dockworkers in the port. These two locations illustrate the multi-scalar and multi-temporal nature of port city space, both above and below the waterline. The essay concludes by going underwater to consider how the beliefs and practices of those in the port city spilled over into the ocean, filling it with both physical detritus and metaphysical entities.